Dekadensi Kaidah Bahasa Indonesia dalam Skripsi Mahasiswa: Urgensi Penguatan Kebijakan Bahasa Indonesia dalam MKWK - Kusumawati, Nira; Suhardi, Suhardi (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2024)
The analysis of this research focuses on proving the form of decadence of Indonesian language rules in student theses, the results of which are correlated with the urgency of strengthening Indonesian language policies as a mandatory curriculum subject in higher education. The data samples in this research came from four student theses from the UNY Lumbung Pustaka page. The decadence of rules in student theses is seen from three components according to EYD V, namely the use of letters, the use of punctuation marks, and the writing of words. The data analysis technique is carried out by carefully reading the thesis, analyzing the forms of errors in the thesis according to EYD V rules, reviewing the data that has been found, concluding the findings, and correlating them with the urgency of strengthening the policy on the substance of Indonesian language studies as a mandatory curriculum subject in higher education. The results of this research show that there are 238 spelling errors in the form of letter usage, 357 errors in the use of punctuation marks, and 254 errors in writing words. These findings indicate the need for strengthening related regulations for implementation signs and the substance of the study or depth of Indonesian language material in compulsory courses in College.